2017
DOI: 10.1161/jaha.116.004542
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Laser Fenestration Is a Feasible Method for Revascularization of Aortic Arch During Thoracic Endovascular Aortic Repair

Abstract: BackgroundReconstruction of the aortic major branches during thoracic endovascular aortic repair is complicated because of the complex anatomic configuration and variation of the aortic arch. In situ laser fenestration has shown great potential for the revascularization of aortic branches. This study aims to evaluate the feasibility, effectiveness, and safety of in situ laser fenestration on the three branches of the aortic arch during thoracic endovascular aortic repair.Methods and ResultsBefore clinical appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 31 publications
3
70
0
Order By: Relevance
“…Unlike fenestration created with a needle and cutting balloon, the use of an energy laser has the potential to decrease the mechanical force required for puncture and the gross integrity of the fabric is always maintained . The graft used in the present study was tested in vivo before its application, and no significant tear was observed during fenestration with the 810 nm fiber lasers, which was consistent with previous research (Supplemental video). During follow‐up, no stent migration or endoleak occurred, which suggested that the connection between fenestration and stent was reliable.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike fenestration created with a needle and cutting balloon, the use of an energy laser has the potential to decrease the mechanical force required for puncture and the gross integrity of the fabric is always maintained . The graft used in the present study was tested in vivo before its application, and no significant tear was observed during fenestration with the 810 nm fiber lasers, which was consistent with previous research (Supplemental video). During follow‐up, no stent migration or endoleak occurred, which suggested that the connection between fenestration and stent was reliable.…”
Section: Discussionsupporting
confidence: 87%
“…Homemade needle, uncontrollable in strength and directional regulation, may also cause harm to surrounding tissue (14). Although current research has indicated that laser or mechanistic needle-guided procedure is effective during ISF for multiple supraaortic arteries (15), the case cohort is small so that the safety of these processes cannot be guaranteed. On the other hand, to substantiate whether QuickFenestrater can be a safer, more effective and efficient alternative than other traditional device for performing ISF to revascularize multiple supraaortic branches during TEVAR necessitates further clinical research.…”
Section: Quick-fenestratermentioning
confidence: 99%
“…Moreover, this procedure requires several readjustments of the C-arm pose (to optimize the viewing direction) which result in prolonged radiation exposure [2]. Finally, fenestrated grafts are customized to fit the patient anatomy, so their fabrication is expensive and time-consuming (tailored process can exceed 6 weeks [4]), and therefore they cannot be used for the emergency treatment of acute syndromes.…”
Section: Introductionmentioning
confidence: 99%